The boundaries of death in Peru: conceptualization and analysis - García Escudero, María del Carmen (2019)
This article is an analysis of the contact of two cultures and their way of perceiving Death: what we have termed borders. I say borders, because in many cases they are almost subtle perceptions between one culture and the other, a clear border, in other cases we can observe adaptations or simplifications of both contexts for a better coexistence, and in other options are unbreakable borders, are omissions of a culture, the border with real history and history told, adapted, or invented. For the analysis, we introduce a new working method that has allowed us, for the studies of the precolonial central Andean region, to investigate data that until now were not taken into account: it has been called dimensionality study. The article is a novel introduction about the moment in which Death forms part of not only a concept to be indoctrinated or changed, but, as we shall see, Death is the representation of a community, its sustenance and balance, evangelization, taking into account the degree he wanted to achieve, could not remove an aspect that cannot be conceptualized, but is a much more complex perception that we will show.